PENGARUH MANAJEMEN LABA DAN MEKANISME CORPORATE GOVERNANCE TERHADAP CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE - Djuitaningsih, Tita; Marsyah, Wahdatul A (Media Riset Akuntansi, 2012)
This  study  aims  to  obtain  empirical  evidence  about  the  effect  of  earning  management and  corporate  governance  mechanism  to  corporate  social  responsibility  disclosure. Corporate  governance  mechanism  was  analyzed  by  board  of  directors,  proportion  of independent  boards  of  directors,  managerial  ownership,  institutional  ownership,  audit committee,  and  number  of  audit  committee  meetings.  The  extent  of  CSR  was  measured used  corporate  social  responsibility  disclosure  index  (  CSRI)  based  on  Global  Reporting Initiative (GRI) reporting standard items which were disclosed in companies annual report and  sustainability report. The population in this research are all non-financial Indonesian firms listed  on Indonesia  Stock Exchange (IDX) and PROPER.  Total  samples  are  63 firms that  selected  using  purposive  sampling  which  were  published  annual  report  and  financial report  among  2008-2010.  The  method  of  analysis  of  this  research  used  multi  regression. The result of this  research  show that earning management and  number of audit committee meetings  had  a  positive  significant  effect  to  corporate  social  responsibility  disclosure. Meanwhile,  board of directors,  proportion  of  independent  boards  of  directors,  managerial ownership,  institutional  ownership  and  audit  committee  had  not  significant  effect  to corporate  social  responsibility  disclosure. Keywords: corporate  social  responsibility  disclosure  index,  earning  management, corporate  governance  mechanism.